Festiwale nauki z perspektywy publiczności: analiza treści programów wydarzeń. - Kołtun, Aleksandra (Avant, 2023)
In the article I am presenting the results of a systematic review of the event programmes of eight science festivals organised in various Polish cities. The aim of the study is to identify the most common forms of festival activities and the scientific disciplines represented. In the paper, I also try to establish whether science festivals go beyond the walls of universities, and to what extent they provide opportunites to interact with the scientists in a relaxed, uninhibited manner (e.g. during workshops). In the course of the analyses I also examine to whether individual scientific fields are in any way particular (e.g. have preferred forms of activity). I use the results as a starting point for further questions: to what extent do festivals go beyond the usual modes of communication in the academy? To what extent does their formula allow us to assume that they reach a broad audience, the so-called society?